On First Volumes and Beginnings in the Study of Psychic Phenomena: Varieties of Investigative Approaches - Alvarado, Carlos S. (Journal of Scientific Exploration, 2015)
<!–[if gte mso 9]> 14.00 <![endif]–> Revue Spirite: Journal d’Études Psychologiques, 1858, Vol. 1, 356 pp. (Freely available online in Google Books http://books.google.com/; paper edition CreateSpace, 2010). Proceedings of the Society for Psychical Research, 1882-1883, Vol. 1, 336 pp. (Freely available online in Google Books http://books.google.com/) Journal of Parapsychology, 1937, Vol. 1, 307 pp. (Available online for a subscription fee in Lexscien http://www.lexscien.org/) Much has been written about the various existing research styles and approaches in science. An example is Alistair Crombie’s Styles of Scientific Thinking in the European Tradition (1993), in which the author presented a widely cited classification that included axiomatic, experimental, and taxonomic approaches to the study of nature, among others (see also Kwa 2005/2011). Similarly, many approaches coexisted during the nineteenth-century in the study of the human experience, as seen in the field of psychology. This brought debates and conflicts between case and experimental studies, as seen in the German and French traditions, respectively (Carroy & Schmidgen 2006) and between the use of introspection and studies based on the study of observable phenomena (Brooks III 1998). As Danzinger (1990) has argued the situation was not simply one of differing approaches, but also one of different assumptions and different social research styles and practices. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>